2021
DOI: 10.1210/jendso/bvab148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Afirma GEC and GSC to Nodules Without Molecular Testing in Cytologically Indeterminate Thyroid Nodules

Abstract: Background Analysis of cytologically indeterminate thyroid nodules with Afirma Gene Expression Classifier (GEC) and Genomic Sequencing Classifier (GSC) can reduce surgical rate and increase malignancy rate of surgically resected indeterminate nodules. Methods Retrospective cohort analysis of all adults with cytologically indeterminate thyroid nodules from January 2013 through December 2019. We compared surgical and malignancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Significant advances have been made in the understanding of cancer molecular pathogenesis, including genetic and epigenetic alterations . Molecular assays, such as real-time polymerase chain reaction (PCR) and next-generation sequencing (NGS), have arisen to detect genomic changes in tumors as novel cancer diagnostic approaches with great potential in the preoperative stratification of malignancy or benignity in thyroid nodules . Most cancer gene variants in most patients occur at intermediate frequencies (2%-20%) or lower .…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances have been made in the understanding of cancer molecular pathogenesis, including genetic and epigenetic alterations . Molecular assays, such as real-time polymerase chain reaction (PCR) and next-generation sequencing (NGS), have arisen to detect genomic changes in tumors as novel cancer diagnostic approaches with great potential in the preoperative stratification of malignancy or benignity in thyroid nodules . Most cancer gene variants in most patients occur at intermediate frequencies (2%-20%) or lower .…”
Section: Introductionmentioning
confidence: 99%
“…There have yet to be any false negatives or false positives. [24][25][26][27][28][29][30][31][32][33][34][35][36] In summary, the article by Randolph et al 11 provides insight into the development and validation of the Afirma RNA sequencing-based classifier for distinguishing MTC from non-MTC samples on thyroid FNAC. It presents a fascinating look into the complex process of machine learning and statistical models used to create such a test.…”
mentioning
confidence: 99%
“…The Afirma RNA sequencing–based MTC classifier described in this text has also been performed on thyroid FNAC specimens from various independent institutions, with more than 2100 thyroid nodules reported in the literature. There have yet to be any false negatives or false positives 24–36 …”
mentioning
confidence: 99%
“…The results showed (at a 24% cancer prevalence): SN -91% [CI, 79-98], SP -68% [CI, 60-76], NPV -96% [CI, [90][91][92][93][94][95][96][97][98][99], PPV -47% [CI, 36-58] (21) (Table 1). Since the validation study, 14 independent real-world studies have been published and in aggregate show a significant improvement in performance over the Afirma GEC, primarily with improved specificity and a higher benign call rate (BCR) of 65% (as compared to 54% with the Afirma GEC) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). As expected, some of these studies have also demonstrated that the implementation of Afirma GSC reduced the rate of surgical intervention by 45-68% (40,43).…”
Section: The Role Of Molecular Diagnostics In Itn For Benign Vs Malig...mentioning
confidence: 77%